Key establish scheme for optical encryption system based on IBE - Ning XU; Geng YANG (Tongxin xuebao)
Based on asymmetric identity-based encryption,a key management mechanism for optical encryption was proposed.First,the IBE scheme,particularly the Boneh-Franklin algorithm was described.Then,the algorithms for key generating,distributing and updating was presented.And the performance of the algorithms in terms of complexity and security was evaluated.Finally,some simulation results about two-dimensional code under two different encryption systems was given,which demonstrate the efficiency,correctness and security of the proposed mechanism.